Connectivity of Greenland halibut in the northwestern Atlantic Ocean inferred from otolith chemistry - Bassi, Laélien; Tremblay, Rejean; Morissette, Olivier; Sirois, Pascal (Frontiers in Marine Science, 2024)
Greenland Halibut (Reinhardtius hippoglossoides) is a deepwater flatfish having a circumpolar distribution. Understanding the spatial connectivity and migratory patterns of this commercially valuable species is essential for ensuring a sustainable fishery; nonetheless, this information remains relatively scarce for many Greenland Halibut populations. Here we evaluate the connectivity and the population structure of halibut along coastal Greenland and Canada to better characterize the contribution of each production zone to the various stocks found in the northwestern Atlantic Ocean. In 2014 and 2016, we sampled 411 large Greenland Halibut from coastal Nunavut, Labrador, and Greenland. We used the elemental fingerprint (magnesium, strontium, and barium) from the otolith core and margin of the sampled fish to determine spatial differentiation of the source areas of the collected halibut. From the 17 sample sites, margin elemental fingerprint delineated four “elemental sectors”, representing pooled adjacent sites having similar chemistry. Overall, 62% of Greenland Halibut were correctly assigned to their sampled coast. Elemental fingerprint of the otolith cores indicated three chemically distinct natal sources for the captured halibut. The chemical record in the otolith cores suggested a high connectivity of Greenland Halibut in the northwestern Atlantic and a main natal source located potentially along the west coast of Greenland. Given that our results suggest the presence of a large nursery around Disko Bay–Hellefiske Bank, protection measures should be considered for this area.